Effectiveness of Land Suitability Program for Special Houses for Disaster Victims in Pasir Sembung Village, Cibeber District, Cianjur Regency - Evelyn Hanaseta; Marningot Tua Natalis Situmorang; Lyna Tania Marlin (Experimental Student Experiences, 2024)
The research delves into the Special Housing Program for Disaster Victims initiated by the Ministry of Public Works and Public Housing. Enforced under the Regulation of the Minister of Public Works and Public Housing No. 20 of 2017, this program focuses on providing specialized housing in Pasir Sembung spanning 1.5 hectares. Managed by the Pasir Sembung Village government, the initiative encompasses the construction of 25 housing units. To ensure efficient implementation, adherence to established guidelines is paramount. Nonetheless, the execution of the special housing plan encountered challenges, notably the reluctance of certain beneficiaries to inhabit the provided dwellings. This study endeavours to evaluate the effectiveness of the disaster victim housing program in Pasir Sembung Village, situated within the Cianjur District of Cianjur Regency. Additionally, it seeks to identify the factors that facilitate or impede the program's success. The study draws upon the 2019 Gibson Effectiveness theory as its theoretical framework. Employing a qualitative research approach involving observation, interviews, and data recording, the study concludes that the special housing program's implementation in Pasir Sembung, Cianjur has not achieved optimal results. Evidently, the program has fallen short of meeting the predetermined benchmarks. This research sheds light on the program's limitations and provides insights into enhancing its efficacy, ultimately contributing to the welfare of disaster-affected communities.